Preparation and Corrosion Resistance of Superhydrophobic Coating on AZ31 Magnesium Alloy - LUO Zhonglong, ZHU Li, ZHANG Peng, RAO Sixian (Cailiao Baohu)
The active properties，easy oxidation and poor corrosion resistance of AZ31 magnesium alloy have always been the biggest challenges in its practical application.In order to improve its corrosion resistance， reduce the corrosion rate and prolong its service life， a stable and corrosion-resistant aluminum phosphate-polymethyl methacrylate (AP/PMMA) superhydrophobic coating was prepared on the surface by impregnation method.The microstructure， chemical composition， phase composition and molecular structure of the coating were analyzed by scanning electron microscope (SEM)，X-ray energy dispersive spectrometer (EDS)，X-ray diffractometer (XRD) and Fourier transform infrared spectrometer (FTIR).Moreover， the hydrophobicity and corrosion resistance were tested by contact angle meter (CA)， Tafel curve and EIS.Results showed that with the increase of immersion time， the contact angle (WCA) of the coating increased first and then decreased.The surface contact angle of the coating prepared by the 60 s immersion sample could reach 154.7 °， showing superhydrophobicity.The surface corrosion current density was 2.289 × 10－9 A/cm2， which was 4 orders of magnitude lower than that of the magnesium substrate.The corrosion potential was increased from－0.941 V to－0.735 V after polishing， indicating that the AP/PMMA superhydrophobic coating could effectively improve the corrosion resistance of AZ31 magnesium alloy.